Low‐angle normal faulting and focused exhumation associated with late Pliocene change in tectonic style in the southern Apennines (Italy). Issue 9 (25th September 2014) - Mazzoli, Stefano; Ascione, Alessandra; Buscher, Jamie T.; Pignalosa, Antonio; Valente, Ettore; Zattin, Massimiliano
Abstract In the southern Apennines, low‐temperature thermochronometry data indicate that exhumation of previous tectonically buried sedimentary units started at around 10 Ma and took place mostly during the last 6 Ma. Relatively high exhumation rates are obtained from apatite fission track (AFT) and (U‐Th)/He (AHe) analysis, pointing to a substantial contribution of tectonic processes to rock exhumation besides erosion. Exhumation rates derived from new apatite (U‐Th)/He data (AHe) for the last 3 Ma are generally lower than rates determined by AFT data and almost in line with erosion rates inferred from cosmogenic nuclides and sediment yield, thus suggesting that tectonic exhumation was dominant during the older exhumation stages of this region. However, younger cooling ages in the Monte Alpi area from both AFT and AHe analyses point out focused exhumation during the last 3 Ma. Structural and morphotectonic analyses indicate that fast exhumation occurred specifically in this area—where the Apulian Platform reservoir carbonates, elsewhere buried beneath a several kilometer‐thick allochthonous cover, are exposed at the surface—as a result of a complex interplay between steep‐rooted reverse faulting and shallow low‐angle extension. This deformation involved the development of foreland‐dipping low‐angle normal faults affecting the allochthonous cover units during the late stages of reverse fault‐related anticlinal growth in the underlying buried carbonates. Extension of the region triggered focused exhumation in the footwall of the extensional low‐angle faults, which was followed by widespread crustal extension and associated development of high‐angle normal faults, leading to surface uplift of Monte Alpi.